2011
DOI: 10.1159/000328770
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient Values Measured by Diffusion-Weighted Imaging Predict Chemoradiotherapeutic Effect for Advanced Esophageal Cancer

Abstract: Background: The purpose of this study was to assess whether apparent diffusion coefficient (ADC) values of esophageal squamous cell carcinoma (ESCC) predict responses to chemoradiotherapy (CRT) and/or patient prognosis. Methods: Magnetic resonance images were acquired to construct the diffusion-weighted images, and the ADC values were calculated before CRT in 80 patients with ESCC. A high-ADC group responded better to CRT than did a low-ADC group (p < 0.01). We divided the 80 patients into two groups based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 37 publications
1
71
5
1
Order By: Relevance
“…Both the univariate and multivariate Cox regression analyses further confirmed this finding. This finding seems to be inconsistent with the study result by Aoyagi et al [17]. They found that the pre-CRT ADC value was a useful marker to predict the therapeutic response and OS for patients with ESCC.…”
Section: Discussioncontrasting
confidence: 81%
“…Both the univariate and multivariate Cox regression analyses further confirmed this finding. This finding seems to be inconsistent with the study result by Aoyagi et al [17]. They found that the pre-CRT ADC value was a useful marker to predict the therapeutic response and OS for patients with ESCC.…”
Section: Discussioncontrasting
confidence: 81%
“…CRT, in particular, can provide a higher treatment effect in comparison to chemotherapy; however, CRT occasionally induces severe advance events. Therefore, it is quite helpful if prediction of the treatment effect of CRT at an early phase can be carried out [6]. Cases that expect a response with early determination of the effects can set accomplishing treatment as the primary goal, while cases that do not expect a response can change the content of treatment and avoid unnecessary adverse events by discontinuing treatment and moving on to the best supportive care.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that DWMRI is useful for gastrointestinal disease [4,5,6,7,8]. DWMRI holds promise for use as a cancer treatment response biomarker because it is sensitive to macromolecular and microstructural changes that can occur at the cellular level earlier than anatomical changes during therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong correlation between ADC values and grade of malignancy has been reported over the last few years in many cancers, including esophageal cancer, in effect validating ADC values as a surrogate for SUV derived from PET [30] . A tantalizing prospect is the possibility of determining disease response with serial ADC values, acquired without risk to the patient, unlike PET-CT the frequency of use of which is limited by concerns over radiation exposure and also cost [31] . Additionally, although both ADC and SUV values correlate with tumor aggressiveness, they repre-sent completely different tumor metrics, and as such it is possible that indeterminate (for malignancy) value with one parameter might be matched with definitive value for the other.…”
Section: Discussionmentioning
confidence: 99%